Spry1 as a novel regulator of erythropoiesis, EPO/EPOR target, and suppressor of JAK2 - Sathyanarayana, Pradeep (American Society of Hematology, 2012)
Sprouty proteins are established modifiers of receptor tyrosine kinase (RTK) signaling and play important roles in vasculogenesis, bone morphogenesis, and renal uteric branching. Little is understood, however, concerning possible roles for these molecular adaptors during hematopoiesis. Within erythroid lineage, Spry1 was observed to be selectively and highly expressed at CFU-e to erythroblast stages. In analyses of possible functional roles, an Mx1-Cre approach was applied to conditionally delete Spry1. At steady state, Spry1 deletion selectively perturbed erythroid development and led to reticulocytosis plus heightened splenic erythropoiesis. When challenged by hemolysis, Spry1-null mice exhibited worsened anemia and delayed recovery. During short-term marrow transplantation, Spry1-null donor marrow also failed to efficiently rescue the erythron. In each anemia model, however, hyperexpansion of erythroid progenitors was observed. Spry function depends on phosphorylation of a conserved N-terminal PY motif. Through an LC-MS/MS approach, Spry1 was discovered to be regulated via the erythropoietin receptor (EPOR), with marked EPO-induced Spry1-PY53 phosphorylation observed. When EPOR signaling pathways were analyzed within Spry1-deficient erythroid progenitors, hyperactivation of not only Erk1,2 but also Jak2 was observed. Studies implicate Spry1 as a novel regulator of erythropoiesis during anemia, transducer of EPOR signals, and candidate suppressor of Jak2 activity.